Comparison of Estrogen Receptor Status and Ki-67 Index in Core Needle Biopsy and Resected Specimen of Breast Carcinoma - E., Geoffrey Sundar; HL, Kishan Prasad; K., Jayaprakash Shetty; Rao, Chandrika; K., Apoorva (Journal of Health and Allied Sciences NU, 2023)
Background and Objectives The status of estrogen receptor (ER), progesterone receptor (PR), human epidermal growth factor receptor 2 (HER2), and Ki-67 expression in core needle biopsy and excision specimens has concurrent results, but many show discordance. However, only a few studies on the subject are available in India. Therefore, this study aims to compare the ER and Ki-67 expression status in core needle biopsy and excision specimens of breast carcinoma.Materials and Methods In this cross-sectional analytical study, 50 breast carcinoma cases were histopathologically examined for ER and Ki-67 expression in both core needle biopsy and excision specimen. The interpreter was blinded for the evaluation of ER and Ki-67 expression index and the data obtained were analyzed using SPSS version 27.Results The average age of the participants was 50 years and breast lump was the most common presenting complaint in all the cases. The concordance rate of histological typing between core needle biopsy and excision specimens was 96%, and the majority were invasive ductal carcinoma (60%) and not otherwise specified (48%) having Nottingham histologic grade 3 (46%). The concordance rate between core needle biopsy and excision specimen for ER and Ki-67 expression was 86% (n = 43) and 54% (n = 27), respectively. Most of the cases were found to be luminal A type (38%). Additionally, the sensitivity, specificity, positive predictive value, and negative predictive value of ER between core needle biopsy and excision specimen were 78.79, 100, 100, and 70.83%, respectively; however, these were 44, 64, 55, and 53.33%, respectively, for Ki-67.Conclusion Although the concordance of the ER status between core needle biopsy and excision specimen was substantial, the discordance rate of Ki-67 was found to be high. Hence, relying solely on core needle biopsy for critical decision-making is inadvisable; however, core needle biopsy can be used as an initial procedure to examine histology and receptor status, Therefore, it is better to reconsider performing immunohistochemistry for the excision specimen, more importantly in ER-negative cases, to benefit the patient with targeted therapy.
Keywords: breast carcinoma; core needle biopsy; estrogen receptor; excision specimen; immunohistochemistry; Ki-67